Model Manajemen Wakaf Uang Dan Pembangunan Infrastruktur di Kabupaten Boalemo - Rahmi Usmaningsih Bolilio, Novika; Sri Dewi Yusuf; Laras Ayu Sekarrini (CV. Ulil Albab Corp, 2026)
This study examines cash waqf as a potential Islamic financial instrument to address budgetary constraints in regional infrastructure development, particularly in Boalemo Regency. Employing a qualitative approach with a case study method, the research aims to analyze an effective and sustainable cash waqf management model that can support local infrastructure financing. Data were collected through in-depth interviews with relevant stakeholders, document analysis, and secondary data review. The findings indicate that although the potential of cash waqf in Boalemo Regency is considerable, its utilization remains suboptimal. The main challenges include limited public awareness and literacy regarding cash waqf, insufficient capacity and professionalism of waqf managers (nazhir), and the absence of adequate local regulations to support productive waqf management. The study concludes that the implementation of cash waqf for infrastructure development requires a transparent, accountable, and integrated governance framework. Furthermore, strong institutional synergy among the Indonesian Waqf Board (BWI), local government, Islamic financial institutions, and the community is essential. Key recommendations include intensifying public socialization and education on cash waqf, strengthening nazhir capacity, formulating supportive local regulations, and leveraging financial technology to enhance fund mobilization and improve monitoring of waqf disbursement for priority infrastructure projects